Prototype of E-Office Administration Letter System In General Part of Government of Tangerang Regency - Supriadi, Ajay; Cahyo Purnomo, Andri; fadilah, wafah (ADI Publisher, 2020)
Along with the development of information and communication technology today, the internet has become a powerful tool to rethink the government system with a new model. However, the application of information technology has not been fully implemented in all fields in the government. One of them is in the General Section of the Regional Secretary of the Tangerang Regency Goverment which still manage the administration of the mail manually and archives the letter data that is still stored in Microsoft Excel. So for that it is necessary to make an information system that can help the work of the General Section Regional Secretary of the Tangerang Regency in managing and filing data letters. The infromation ssytem that will be built later will store data letters that have been inputted into the database so that the stored data will be safer and easier when searching for data. E-Office is a system related to office administration that is done electronically and uses the help of communication device and information system. With the creation of this system, it will be able to assist in the administration of correspondence to make it easier, faster and more accurate